China Financial Sector Assessment - World Bank (World Bank, Washington, DC, 2017)
Since the 2011 financial sector assessment program (FSAP), China’s economic growth has remained strong, although a necessary economic transformation is underway. China now has the world’s largest gross domestic product (GDP) in public private partnership (PPP) terms, and poverty rates have fallen. However, medium-term growth prospects have moderated. The economic transformation requires a fundamental change in the role of the financial system. Although longer-term objectives are clear, policymakers continue to face challenges in balancing short-term growth concerns with long-term financial stability and sustainability. The slow pace of state-owned enterprise (SOEs) reform and limited exit of weak firms have resulted in efficiency losses and reinforced the perception of implicit guarantees. Contingent fiscal liabilities have also grown rapidly. Addressing these tensions is challenging in the context of the strong presence of the state in the financial sector. Maintaining financial stability will also require that remaining gaps in regulatory frameworks be addressed. Further enhancements to crisis management frameworks are needed to allow financial institutions to fail in a manner that minimizes the impact on financial stability and public resources.